THE INFLUENCE OF COMPETENCE AND TRAINING ON EMPLOYEE PERFORMANCE AT PT. ARIEF NIRWANA MAIN TAPIN DISTRICT, SOUTH KALIMANTAN - Dedy Arief Budiman; Surachmad, Surachmad (Sean Institute, 2021)
This study aims to analyze: 1) the partial influence of competence and training on employee performance, 2) the simultaneous influence of competence and training on employee performance, and 3) which variable, competence or training, has the most dominant influence on employee performance at PT. Arief Nirwana Utama, Tapin Regency. The sample consisted of 60 respondents selected using a stratified proportional random sampling technique. The regression analysis resulted in the equation Y=32552+0.213X1+0.131X2Y = 32552 + 0.213X_1 + 0.131X_2Y=32552+0.213X1+0.131X2. Partial testing showed that competence (X1) positively and significantly affects performance (Y), with tcalculated =2.450> ttable =2.003t_calculated = 2.450 > t_table = 2.003tcalculated=2.450> ttable =2.003. However, training (X2) had a positive but insignificant effect on performance, with tcalculated =1.939< ttable =2.003t_calculated = 1.939 < t_table = 2.003tcalculated=1.939< ttable =2.003. Thus, the first hypothesis (H1) is only proven for the competence variable. The multiple correlation analysis showed an RRR value of 0.672, indicating a fairly strong and positive relationship between competence (X1), training (X2), and performance (Y). The coefficient of determination (R2R^2R2) was 45.2%, meaning these variables contributed 45.2% to employee performance, with the remaining 54.8% influenced by other factors. The simultaneous test ( Fcalculated =23.514> Ftable =3.154F_calculated = 23.514 > F_table = 3.154Fcalculated=23.514> Ftable =3.154) demonstrated that competence and training together significantly influence performance, proving the second hypothesis (H2 ). Competence (X1), with a regression coefficient of 0.213, was more dominant than training (X2), which had a coefficient of 0.131. This confirms the third hypothesis (H3) that competence has the most dominant effect on employee performance.